Durable Li2CN2 Solid Electrolyte Interphase Wired by Carbon Nanodomains via In Situ Interface Lithiation to Enable Long‐Cycling Li Metal Batteries. (10th November 2022) - Yang, Qifan; Hu, Jiulin; Yao, Zhenguo; Liu, Jianjun; Li, Chilin
Abstract: Lithium metal batteries (LMBs) are becoming the promising candidate of high‐energy storage systems. However, the fragile natural solid electrolyte interphase (SEI) cannot retard the Li dendrite growth at anode, which will cause the low coulombic efficiency (CE) of Li plating/stripping and safety hazards in LMBs. Here, an in situ construction strategy of novel artificial SEI consisting of Li2 CN2 ionic conductor wired by carbon nanodomains via dicyandiamide solution reaction method on Li metal surface is proposed. This lithiophilic Li2 CN2 has the higher anti‐reduction stability and longer critical length for Li dendrite, showing the excellent dendrite suppressing ability. The wired carbon domains promote the electron connection and charge homogenization in SEI, leading to the uniform Li nucleation around Li2 CN2 /C grains with enhanced interface kinetics and reduced polarization. This dual conductive Li2 CN2 /C network enables the durable preservation of high CE and low voltage hysteresis during Li plating/stripping, endowing LiNi0.8 Mn0.1 Co0.1 O2 /Li cells with ultralong cycling life exceeding 1000 cycles at high rate. The cycling stabilization effect is also remarkable even under thin Li anode and high‐loading cathode conditions. This study provides a solution to robust SEI configuration of high conductivity via in situ interface lithiation reaction for high‐performance LMBs. Abstract : An in situ construction strategy of novel artificial SEI consisting of Li2 CN2 ionic conductor wired by carbon nanodomains is proposed via dicyandiamide solution reaction method on Li metal surface. This dual conductive Li2 CN2 /C network enables the durable preservation of high coulombic efficiency and low voltage hysteresis during Li plating/stripping, endowing LiNi0.8 Mn0.1 Co0.1 O2 /Li cells with ultralong cycling life.